Regulation of nucleolus assembly by non-coding RNA polymerase II transcripts - Caudron-Herger, Maïwen; Pankert, Teresa; Rippe, Karsten (Nucleus, 2016)
The nucleolus is a nuclear subcompartment for tightly regulated rRNA production and ribosome subunit biogenesis. It also acts as a cellular stress sensor and can release enriched factors in response to cellular stimuli. Accordingly, the content and structure of the nucleolus change dynamically, which is particularly evident during cell cycle progression: the nucleolus completely disassembles during mitosis and reassembles in interphase. Although the mechanisms that drive nucleolar (re)organization have been the subject of a number of studies, they are only partly understood. Recently, we identified Alu element-containing RNA polymerase II transcripts (aluRNAs) as important for nucleolar structure and rRNA synthesis. Integrating these findings with studies on the liquid droplet-like nature of the nucleolus leads us to propose a model on how RNA polymerase II transcripts could regulate the assembly of the nucleolus in response to external stimuli and during cell cycle progression.
Gesehen am 29.04.2020